# Find dydx, if y = (3x-1)(2x+3)(5-x)23 - Mathematics and Statistics

Sum

Find ("d"y)/("d"x), if y = root(3)(((3x - 1))/((2x + 3)(5 - x)^2)

#### Solution

y = root(3)(((3x - 1))/((2x + 3)(5 - x)^2)

= (3x - 1)^(1/3)/((2x + 3)^(1/3)*(5 - x)^(2/3)

Taking logarithm of both sides, we get

log y = log[(3x - 1)^(1/3)/((2x - 3)^(1/3)*(5 - x)^(2/3))]

= log(3x - 1)^(1/3) - [log(2x + 3)^(1/3) + log(5 - x)^(2/3)]

= 1/3log(3x - 1) - [1/3 log(2x + 3) + 2/3log(5 - x)]

Differentiating both sides w.r.t. x, we get

"d"/("d"x)(log y) = 1/3*"d"/("d"x)[log(3x - 1)] - 1/3*"d"/("d"x)[log(2x + 3)] - 2/3*"d"/("d"x)[log(5 - x)]

∴ 1/y*("d"y)/("d"x) = 1/3*1/((3x - 1))*"d"/("d"x)(3x - 1) - 1/3*1/((2x + 3))*"d"/("d"x)(2x + 3) - 2/3*1/((5 - x))*"d"/("d"x)(5 - x)

∴ 1/y*("d"y)/("d"x) = 1/(3(3x - 1)) xx (3 - 0) - 1/(3(2x + 3)) xx (2 + 0) - 2/(3(5 - x)) xx (0 - 1)

∴ 1/y*("d"y)/("d"x) = 1/(3x - 1)- 2/(3(2x + 3)) + 2/(3(5 - x))

∴ ("d"y)/("d"x) = y/3[3/(3x - 1) - 2/(2x + 3) + 2/(5 - x)]

∴ ("d"y)/("d"x) = 1/3 root(3)((3x - 1)/((2x + 3)*(5 - x)^2)) [3/(3x - 1) - 2/(2x + 3) + 2/(5 - x)]

Concept: The Concept of Derivative - Derivatives of Logarithmic Functions
Is there an error in this question or solution?
Chapter 1.3: Differentiation - Q.5
Share